Uncomfortable conversations with a black man [compact disc, unabridged] - Acho, Emmanuel (Macmillan Audio, 2020)
Emmanuel Acho takes on all the questions, large and small, insensitive and taboo, many White Americans are afraid to ask, yet which all Americans need the answers to, now more than ever. With the same open-hearted generosity that has made his video series a phenomenon, Acho explains the vital core of such fraught concepts as white privilege, cultural appropriation, and 'reverse racism.' In his own words, he provides a space for compassion and understanding in a discussion that can lack both. He asks only for the listener's curiosity, but along the way, he will galvanize everyone to join the antiracist fight.